AN URGENCY TO ARRANGE THE MEETING OF FOUNDATION FOUNDERS THROUGH TELECONFERENCE MEDIA? - Andi Suci Wahyuni; Mukaromah; Amina Rahma Ahmad; Imam Hidayat; Afif Athaullah (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
Each legal entity has distinctive characteristics for each of its organizations. Not all legal entities make members’ meetings one of the organizational tools. The same applies to Foundations and their organs. This is different from the position of the GMS and the Cooperative Member Meeting. Digital transformation in community and organizational activities has been increasingly massive since the Covid-19 pandemic. This study examined organizing the meeting of the Foundation's supervisors through virtual meetings. This research was normative research using a conceptual approach, a statutory approach, and a comparative approach. The results indicate that there is a need for strict regulation in the legislation related to the mechanism of the Foundation's supervisory meeting which is carried out through teleconference. Due to the anticipation of the law that is in line with the development of the reality of the interaction of legal subjects who are no longer affected by territorial boundaries.